Nisin Resistance of Listeria monocytogenes Is Increased by Exposure to Salt Stress and Is Mediated via LiaR - Bergholz, Teresa M. (American Society for Microbiology, 2013)
Growth of Listeria monocytogenes on refrigerated, ready-to-eat food is a significant food safety concern. Natural antimicrobials, such as nisin, can be used to control this pathogen on food, but little is known about how other food-related stresses may impact how the pathogen responds to these compounds. Prior work demonstrated that exposure of L. monocytogenes to salt stress at 7°C led to increased expression of genes involved in nisin resistance, including the response regulator liaR. We hypothesized that exposure to salt stress would increase subsequent resistance to nisin and that LiaR would contribute to increased nisin resistance. Isogenic deletion mutations in liaR were constructed in 7 strains of L. monocytogenes, and strains were exposed to 6% NaCl in brain heart infusion broth and then tested for resistance to nisin (2 mg/ml Nisaplin) at 7°C. For the wild-type strains, exposure to salt significantly increased subsequent nisin resistance (P < 0.0001) over innate levels of resistance. Compared to the salt-induced nisin resistance of wild-type strains, ΔliaR strains were significantly more sensitive to nisin (P < 0.001), indicating that induction of LiaFSR led to cross-protection of L. monocytogenes against subsequent inactivation by nisin. Transcript levels of LiaR-regulated genes were induced by salt stress, and lmo1746 and telA were found to contribute to LiaR-mediated salt-induced nisin resistance. These data suggest that environmental stresses similar to those on foods can influence the resistance of L. monocytogenes to antimicrobials such as nisin, and potential cross-protective effects should be considered when selecting and applying control measures for this pathogen on ready-to-eat foods.